From North to South : Southern Scholars Engage with Edward Schillebeeckx. - Bergin, Helen F. (ATF Press, 2013)
From North to South brings together the interests in Edward Schillebeeckx of eight theologians from Australia, New Zealand and Malaysia. In each chapter, theologians dialogue from a southern context with one of Schillebeeckx's themes or methods. Themes such as suffering and negative contrast experiences, political holiness, ecclesiology, God and the cross, resurrection and hope, and theology and culture are addressed. Attention to Schillebeeckx's hermeneutics lies at the heart of several chapters but is generally woven throughout. Contributors bring their particular southern contexts into seri.